Effects and costs of real-time cardiac telerehabilitation: randomised controlled non-inferiority trial. Issue 2 (27th August 2018) - Maddison, Ralph; Rawstorn, Jonathan Charles; Stewart, Ralph A H; Benatar, Jocelyne; Whittaker, Robyn; Rolleston, Anna; Jiang, Yannan; Gao, Lan; Moodie, Marj; Warren, Ian; Meads, Andrew; Gant, Nicholas
Abstract : Objective: Compare the effects and costs of remotely monitored exercise-based cardiac telerehabilitation (REMOTE-CR) with centre-based programmes (CBexCR) in adults with coronary heart disease (CHD). Methods: Participants were randomised to receive 12 weeks of telerehabilitation or centre-based rehabilitation. REMOTE-CR provided individualised exercise prescription, real-time exercise monitoring/coaching and theory-based behavioural strategies via a bespoke telerehabilitation platform; CBexCR provided individualised exercise prescription and coaching via established rehabilitation clinics. Outcomes assessed at baseline, 12 and/or 24 weeks included maximal oxygen uptake (V̇O2 max, primary) modifiable cardiovascular risk factors, exercise adherence, motivation, health-related quality of life and programme delivery, hospital service utilisation and medication costs. The primary hypothesis was a non-inferior between-group difference in V̇O2 max at 12 weeks (inferiority margin=−1.25 mL/kg/min); inferiority margins were not set for secondary outcomes. Results: 162 participants (mean 61±12.7 years, 86% men) were randomised. V̇O2 max was comparable in both groups at 12 weeks and REMOTE-CR was non-inferior to CBexCR (REMOTE-CR-CBexCR adjusted mean difference (AMD)=0.51 (95% CI −0.97 to 1.98) mL/kg/min, p=0.48). REMOTE-CR participants were less sedentary at 24 weeks (AMD=−61.5 (95% CI −117.8 to −5.3) min/day, p=0.03), while CBexCR participants had smaller waist (AMD=1.71 (95% CI 0.09 to 3.34) cm, p=0.04) and hip circumferences (AMD=1.16 (95% CI 0.06 to 2.27) cm, p=0.04) at 12 weeks. No other between-group differences were detected. Per capita programme delivery (NZD1130/GBP573 vs NZD3466/GBP1758) and medication costs (NZD331/GBP168 vs NZD605/GBP307, p=0.02) were lower for REMOTE-CR. Hospital service utilisation costs were not statistically significantly different (NZD3459/GBP1754 vs NZD5464/GBP2771, p=0.20). Conclusion: REMOTE-CR is an effective, cost-efficient alternative delivery model that could—as a complement to existing services—improve overall utilisation rates by increasing reach and satisfying unique participant preferences.